Evaluation of Pedestrian Behavior on Mid-block Crosswalks: A Case Study in Fortaleza—Brazil - Torres, Caio; Sobreira, Lucas; Castro-Neto, Manoel; Cunto, Flávio; Vecino-Ortiz, Andrés; Allen, Katharine; Hyder, Adnan; Bachani, Abdulgafoor (Frontiers in Sustainable Cities, 2020)
In urban streets, pedestrians compete with vehicles for right-of-way. In some situations, it may be very challenging for pedestrians to deal with complex, sometimes hostile, traffic conflicts, especially in urban areas. This paper provides an exploratory analysis of pedestrian behavior on four types of mid-blocks crossing facilities in the city of Fortaleza, Brazil. The analysis was based on descriptive statistics and logistic regression models of variables related to signal control, facilities, and pedestrian characteristics and behavior. The models considered the following binary variables: (i) crossing vs no crossing while pedestrian red phase; (ii) driver yielded vs did not yield while pedestrian crossing; (iii) normal vs aggressive/risked pedestrian behavior while crossing. A total of 2,400 crossings were considered in this study. The results showed that, in general, the increase of traffic demand is related to easier crossings. Moreover, the presence of raised crosswalks increased in about 20 times the number of drivers that yielded to pedestrians in comparison to the only-marked site. As well as the implementation of mechanisms that help the performance of crossings, like raised platforms or traffic signals, reduced considerably the number of aggressive/risked crossings.